Intra-industry information transfers associated with earnings releases - Foster, George (Journal of Accounting and Economics, 1981)
The impact that a firm's earnings releases have on the stock prices of other firms in its industry is examined. For an identifiable sub-set of firms, the results are consistent with a significant information transfer occurring between the earnings release firm and the other firms in its industry. This subset is identified by examining the impact of the release on the stock price of the announcing firm. The magnitude of this impact is more significant for a sample of firms which have a larger percentage of their revenues in the same line of business as the earnings release firm vis-á-vis a sample with a lower percentage of their revenues from the same line of business. Alternative interpretations of the empirical results are also discussed. The research findings have implications for information content and market efficiency research and for research on policy issues associated with disclosure regulation.